Struktur komunitas kutu putih (Hemiptera: Pseudococcidae) dan musuh alaminya pada tanaman singkong (Manihot esculenta Crantz) di Kecamatan Ciampea dan Sukaraja, Kabupaten Bogor, Jawa Barat: Community structure of mealybugs (Hemiptera: Pseudococcidae) and their natural enemies on cassava plants (Manihot esculenta Crantz) in Ciampea and Sukaraja Subdistrict, Bogor, West Java - Putri Indah Wahyuni; Dadan Hindayana; Sartiami, Dewi; Lexi Majesty Pendong (Jurnal Entomologi Indonesia, 2025)
Cassava is one of the food commodities in Indonesia, but its productivity often decreases due to mealybug attacks (Hemiptera: Pseudococcidae). This study aims to determine the type and abundance of mealybugs and the ecological relationships between them and their natural enemies on cassava plants. The sampling method employed was purposive sampling, involving the selection of 100 sample plants per location, namely Benteng Village and Pasirlaya Village, in Bogor Regency. Mealybug and parasitoid samples were taken from three infested leaves, while predators were collected from the plant canopy. Identification was carried out morphologically to the species level, analyzed using the ecological index, and compared using the Mann-Whitney test (P = 0.05). The study’s results identified four species of mealybugs: Paracoccus marginatus Williams & Granara de Willink, Ferrisia virgata (Cockerell), Pseudococcus jackbeardsleyi (Gimpel & Miller), and Phenacoccus manihoti Matile-Ferrero. Natural enemies of mealybugs found from the predator group were Cryptolaemus montrouzieri Mulsant, Plesiochrysa ramburi (Schneider), Scymnus sp.1, Scymnus sp.2, Theridion sp., and from the parasitoid group, namely Anagyrus lopezi (De Santis), Acerophagus papayae Noyes & Schauff. The diversity, evenness, and richness indices of arthropod species were higher in Pasirlaya, while dominance was higher in Benteng. The parasitization rate of A. papayae and A. lopezi was more stable in Pasirlaya, although the arthropod population did not differ significantly between locations (P = 0,31). This study concluded that Pa. marginatus and Ph. manihoti were the dominant mealybug species, with predators Theridion sp. and C. montrouzieri as the most abundant natural enemies, The parasitoid A. lopezi was known to parasitize Ph. manihoti, and A. papayae parasitized Pa. marginatus.